2005
DOI: 10.1007/s11104-005-2888-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mycorrhizal fungus Glomus intraradices on uranium uptake and accumulation by Medicago truncatula L. from uranium-contaminated soil

Abstract: Phytostabilization strategies may be suitable to reduce the dispersion of uranium (U) and the overall environmental risks of U-contaminated soils. The role of Glomus intraradices, an arbuscular mycorrhizal (AM) fungus, in such phytostabilization of U was investigated with a compartmented plant cultivation system facilitating the specific measurement of U uptake by roots, AM roots and extraradical hyphae of AM fungi and the measurement of U partitioning between root and shoot. A soil-filled plastic pot constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
(42 reference statements)
1
15
0
1
Order By: Relevance
“…The high percentage of root colonization in the inoculated treatment indicated that dandelion formed a strong symbiosis with R. irregularis. Similar to previous work (Mäder et al, 1993;Chen et al, 2005;Chen et al, 2007a), mycelia developed well in the inoculated treatment and passed through the 37-µm nylon net and PTFE to the HC. Some hyphae, probably dead or saprophytic, were detected in soils of the uninoculated treatments, and were also considered to be present in the inoculated treatments.…”
Section: Discussionsupporting
confidence: 75%
“…The high percentage of root colonization in the inoculated treatment indicated that dandelion formed a strong symbiosis with R. irregularis. Similar to previous work (Mäder et al, 1993;Chen et al, 2005;Chen et al, 2007a), mycelia developed well in the inoculated treatment and passed through the 37-µm nylon net and PTFE to the HC. Some hyphae, probably dead or saprophytic, were detected in soils of the uninoculated treatments, and were also considered to be present in the inoculated treatments.…”
Section: Discussionsupporting
confidence: 75%
“…Glomus intraradices increased root U concentration and content, but decreased shoot U concentrations. AM fungi and root hairs improved not only P acquisition but also root uptake of U, and the mycorrhiza generally decreased U translocation from plant root to shoot (Rufyikiri et al, 2004;Chen et al 2005a, b).…”
Section: Mycoremediation and The Mycorrhizospherementioning
confidence: 99%
“…The results of Rufyikiri et al (2004b) were corroborated by those obtained by Chen et al (2005aChen et al ( ,b,d, 2006 who observed an increased U immobilization in roots, a lower U accumulation in shoots and consequently, a lower translocation of U from rootto-shoot when plants were colonized by AM fungi. Chen et al (2005d) also noticed, using a compartmented pot system, that more U was partitioned to the shoots of Medicago truncatula when roots and hyphae could take up U than when only hyphae could develop in the contaminated soil compartment. This indicated that U taken up through the root pathway could be more easily translocated to the shoots than when U was taken up by the fungal hyphae.…”
Section: Influence Of Am Fungi On Root-to-shoot U Translocationmentioning
confidence: 91%